DIMENSI PENGUKURAN KUALITAS HIDUP DI BEBERAPA NEGARA - Jamaruddin Jamaruddin; Sudirman Sudirman (Jurnal Pallangga Praja (JPP), 2022)
The measurement of quality of life is different because there is no concept of quality of life agreedupon by experts because quality of life is seen as complex and does not apply as a whole, includingcultural factors. Therefore, to determine the quality of life of a country, United Nation DevelopmentProgram (UNDP) measures the quality of life through the Human Development Index (HDI), whichmeasures the quality of life objectively, however, the World Health Organization (WHO) and theHappiness Index has tend to measure the quality of life subjectively. This discussion tries to revealthe dimensions in measuring the quality of life such as government organizations, internationalinstitutions including the results of research by experts in various countries.